Arbetsnorm, kön och kunskap inom fiskeriet (Sociologisk Forskning, 1997)
Gender, norm and knowledge in the fishing industryThis article deals with the position of women fishplant workers in Iceland. We focus primarily on women’s work in freezing plants but also consider their position in Icelandic society. In our analysis of women’s position in the fishery we examine such aspects as work norms, definitions of skill, and division of labour. We show that there is a clear gender division of labor, and jobs are defined as womanly or manly. Women's work is valued less and is not seen as requiring skill but feminine qualities. In the freezing plants women are under more constant pressure during their work than men are and their work has become increasingly monotonous. They combine wage work with housework and many of them are single mothers who work full time. Having a strong work ethic these women do not complain in spite of hard work and low wages. By examining women's position in the fishery we find that gender inequality is not only maintained by low wage and double day but is an integral part of the work process in the fish plants.